2015
DOI: 10.1371/journal.pone.0138803
|View full text |Cite
|
Sign up to set email alerts
|

Monoconjugation of Human Amylin with Methylpolyethyleneglycol

Abstract: Amylin is a pancreatic hormone cosecreted with insulin that exerts unique roles in metabolism and glucose homeostasis. The therapeutic restoration of postprandial and basal amylin levels is highly desirable in diabetes mellitus. Protein conjugation with the biocompatible polymer polyethylene glycol (PEG) has been shown to extend the biological effects of biopharmaceuticals. We have designed a PEGylated human amylin by using the aminoreactive compound methoxylpolyethylene glycol succinimidyl carbonate (mPEGsc).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…However, the pharmacology reported for these cell lines is not straight forward. Despite this, MCF‐7 cells have been used in several studies as an amylin receptor model (Sisnande et al, ; Shi et al, ). These cells are reported to express mRNA encoding two distinct splice variants of CTR, RAMP1 and RAMP3 (Chen et al, ; Ellegaard et al, ).…”
Section: The Challenges Of Pharmacology In Non‐transfected Cell Systemsmentioning
confidence: 99%
“…However, the pharmacology reported for these cell lines is not straight forward. Despite this, MCF‐7 cells have been used in several studies as an amylin receptor model (Sisnande et al, ; Shi et al, ). These cells are reported to express mRNA encoding two distinct splice variants of CTR, RAMP1 and RAMP3 (Chen et al, ; Ellegaard et al, ).…”
Section: The Challenges Of Pharmacology In Non‐transfected Cell Systemsmentioning
confidence: 99%
“…Formulating monomeric insulin requires new excipients, which do not promote the R 6 hexamer, but still imbue insulin with sufficient stability to prevent aggregation and denaturation over time. [24,25] Covalent PEGylation has been successful as a strategy to stabilize insulin in formulation; [26][27][28] however, the extended pharmacokinetics in vivo associated with PEGylation is not desirable for rapid acting insulins. [29] Recent research has demonstrated non-covalent modification of proteins as a strategy to enhance their stability in formulation.…”
Section: Introductionmentioning
confidence: 99%
“…A new class of excipients are needed for protein formulation to address concerns surrounding aggregation and denaturation over time. [ 25 , 26 ] Covalent PEGylation has been successful as a strategy to stabilize insulin and amylin in formulation; [ 27 29 ] however, covalent modification of proteins often interferes with their activity, typically extends their pharmacokinetics in vivo , and can lead to increased immunogenicity. [ 30 ] Recent research has shown that non-covalent modification of proteins can enhance their stability in formulation.…”
mentioning
confidence: 99%